Student Team Achievement Division dalam Meningkatkan Hasil Belajar Siswa - Jufri, Muhammad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
The importance of this research was the essence of learning trough student team achievement division and the implementation steps that have not been done on the research object. The level of learning was decided by students that still need to be maximized to achieve the minimum completion criteria established by the school. The objective of the research is to know the form of implementation and effetiveness of learning trough Student Team Achievement Division in improving the outcomes (result) of learning lslamic Religion Education for the eleventh grade on SMK Negeri 1 Parepare. The research setting used in this research was a classroom action research which was conducted cyclically with experimental approach. The subjects of this research are the eleventh grade on SMK Negeri 1 Parepare and the numbers of the subjects were 25 student. The method of data collection as research instrument was tes, participant observation sheet, and documentation, the data analysis technique used.frequency distribution analysis. The research result found that Student Team Achievement Division (STAD) as learning strategy was effetive to improve the students learning outcomes of the eleventh grade of SMK Negeri I Parepare